Covid-19 and Technology - Mauro Caselli; Andrea Fracasso (Global Labor Organization (GLO), 2021)
This contribution reviews the rich interdisciplinary literature covering the relationship between the diffusion of COVID-19 and the adoption of technologies in various sectors of the economy, ranging from health care facilities to manufacturing companies. Besides covering the technical and technological progress achieved to enhance contact tracing, tracking and mapping with the intent of stopping the diffusion of the disease, this chapter also discusses the wide range of innovations introduced to detect the disease and treat the affected people. Finally, the analysis addresses how companies and institutions adopted various technologies (from advanced robotics to artificial intelligence) to mitigate the adverse effects of the virus on their employees, customers, and suppliers, as well as to preserve uncontaminated environments and enforce personal distancing in the workplace. In most cases, modern technologies played a key role to transform workplaces, human resource management, production and sale networks. This contribution points out that, notwithstanding its beneficial effects, the rapid and widespread diffusion of new technologies poses serious challenges as to their appropriate use once the pandemic will be over (i.e., privacy data protection and fundamental rights) and their long-lasting and transformative effects on both social and industrial relations.
Keywords: O14; O31; O33; I10; J24; 330; COVID-19; technology; health; labor; firms